Ventricular-arterial coupling as a potential therapeutic target in diabetes - Saeed, Sahrai; Holm, Hannes; Nilsson, Peter (Journal of the Pakistan Medical Association, 2021)
Patients with type 2 diabetes (T2D) are at high risk of cardiovascular complications. Novel anti-diabetic medications such as sodium-glucose cotransporter-2 inhibitors (SGLT-2i) and Glucagon-like peptide-1 receptor agonists (GLP-1RA) have been shown to possess cardiac and renal protective effects beyond their ability to lower plasma glucose. Use of SGLT-2i and GLP-1RA in patients with T2D and heart failure reduce cardiovascular risk and heart failure related hospitalizations. SGLT-2i treatment has shown to improve the long-term prognosis of patients with heart failure. Both drugs also have the potential to normalize ventricular-arterial coupling (VAC). VAC is the crosstalk between the left ventricular function and the arterial system, and is an indicator of the global cardiovascular performance. In this overview, we will describe the concept of VAC and the features of diabetic cardiomyopathy, as well as VAC as a potential therapeutic target in diabetes by use of novel anti-diabetic drugs, primarily SGLT-2i and GLP-1RA. Continuous...